Causal Factors of Easting Disorder Behaviors in Adolescent Females - Sarah Barker; Bonnie Ahn (Undergraduate Research Journal for the Human Sciences, 2016)
This study aims to identify the relationships of psychological, cultural, biological, and environmental factors with the development of eating disorder behaviors among adolescent females. We hypothesize that individuals’ psychological, cultural, biological, and environmental factors differentially influence the development of eating disorder behaviors among adolescent females. The present study will employ an explanatory approach using a cross-sectional study design with a sample of 100 adolescent females ages 12-18 across southern Louisiana school campuses. There will be two instruments used, the Body-Image Ideals Questionnaire (BIQ) created by Thomas Cash and Marcela Szymanski (1995) and a self-made questionnaire. The BIQ aims to identify correlation between body image, personality traits, and psychological attributes linked to eating disorders. The self-made questionnaire will search for relationships between cultural and environmental factors with the development of eating disorders. Multiple regression analysis will be performed to address the study’s hypothesis.
Keywords: Eating; Disorders; Female